Sexual dysfunction precedes motor defects, dopaminergic neuronal degeneration, and impaired dopamine metabolism: Insights from Drosophila model of Parkinson’s disease - Koza, Zevelou; Ayajuddin, Mohamad; Das, Abhik; Chaurasia, Rahul; Phom, Limamanen; Yenisetti, Sarat Chandra (Frontiers in Neuroscience, 2023)
Sexual dysfunction (SD) is one of the most common non-motor symptoms of Parkinson’s disease (PD) and remains the most neglected, under-reported, and under-recognized aspect of PD. Studies have shown that Dopamine (DA) in the hypothalamus plays a role in regulating sexual behavior. But the detailed mechanism of SD in PD is not known. Drosophila melanogaster shares several genes and signaling pathways with humans which makes it an ideal model for the study of a neurodegenerative disorder such as PD. Courtship behavior of Drosophila is one such behavior that is closely related to human sexual behavior and so plays an important role in understanding sexual behavior in diseased conditions as well. In the present study, a sporadic SD model of PD using Drosophila was developed and SD phenotype was observed based on abnormalities in courtship behavior markers. The Drosophila SD model was developed in such a way that at the window of toxin treatment, it does not exhibit mobility defects but shows SD. The whole brain tyrosine hydroxylase immunostaining showed no observable dopaminergic (DAergic) degeneration (number of DA neurons and fluorescence intensity of fluorescently labeled secondary antibodies that target anti-TH primary antibody) of the SD model. Similarly, there was no significant depletion of brain DA and its metabolite levels (HVA and DOPAC) as determined using ECD-HPLC (High Performance Liquid Chromatography using Electrochemical Detector. The present study illustrates that the traits associated with courtship and sexual activity provide sensitive markers at the earlier stage of PD onset. This fly model of SD throws an opportunity to decipher the molecular basis of SD under PD conditions and to screen nutraceuticals/potential therapeutic molecules to rescue SD phenotype and further to DAergic neuroprotection.